2007
DOI: 10.1136/vr.160.23.787
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic signs of renal disease in rabbits

Abstract: The radiological features of 65 rabbits with suspected renal disease are reviewed. The radiological features included a generalised increase in bone opacity (osteosclerosis), renomegaly, nephroliths, ureteroliths and soft tissue mineralisation. One or more of these changes were present on radiographs of 57 of the 65 rabbits. Renal disease was suspected because of the clinical signs and the presence of kidney stones and/or high blood concentrations of urea and creatinine. Significant renal disease was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
(15 reference statements)
3
23
0
1
Order By: Relevance
“…In our study, serum creatinine (p<0.001) and BUN (p<0.01) levels were found to have a statistically significant relationship with the serological status of rabbits (Table 1). Our results are consistent with those of previous studies (1,3,10,33). On the other hand, numerous studies have reported that blood biochemistry parameters can be used to measure differences between animals.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, serum creatinine (p<0.001) and BUN (p<0.01) levels were found to have a statistically significant relationship with the serological status of rabbits (Table 1). Our results are consistent with those of previous studies (1,3,10,33). On the other hand, numerous studies have reported that blood biochemistry parameters can be used to measure differences between animals.…”
Section: Discussionsupporting
confidence: 94%
“…In clinically healthy rabbits, the present study showed that the seropositivity rate for E. cuniculi infection was 49.5%, which is similar to rates (50-53%) of infection in previous studies (6,14,20), although it is higher than the rates of infection reported in some (4,13,17,26,28,(30)(31)(32). In contrast, in the current study, the seropositivity rate of the disease was lower than those previously reported (71-93%) in various countries (3,10,21,37). Serostatus was also investigated by sex, and no difference was found between sexes in terms of seropositivity (Fig 1).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In rabbits suffering from dental disease, the pathophysiological relationship among orthodontic, periodontal and endodontic lesions is unclear (Verstraete & Osofsky 2005) and appears to be much more complex than in other mammals. Most likely, multiple factors are involved in the development of a syndrome of acquired dental disease such as traumatic injuries of the orofacial area, less abrasive diet, reduced chewing movements, altered chewing actions, changes in the structure and adaptability of the chewing muscles, temporomandibular joint disorders, inappropriate dietary phosphorus, inappropriate dietary calcium, malabsorption and systemic disease (Poikela et al 2000, Harcourt-Brown 2002, Crossley & Aiken 2003, Fujisawa et al 2003, Langenbach et al 2003, Crossley 2005, Harcourt-Brown 2007a,b, Wolf & Kamphues 2009).…”
Section: Rabbit Dental Diseasementioning
confidence: 99%
“…Nicht selten wird im Vorbericht von Kleintieren mit renaler Azotämie Polydipsie/Polyurie erwähnt [42]. Dies ist bei Kaninchen und Nagern seltener der Fall [16] [30]. Das spezifische Harngewicht von Tieren mit länger bestehender renaler Azotämie, die meist bei chronischen Nierenerkrankungen vorliegt, liegt oft im Bereich von 1007-1013 [40].…”
Section: Diagnose Einer Renalen Azotämieunclassified